Influence of point-of-use filters and stagnation on water quality at a preschool and under laboratory conditions. (1st March 2022) - Clark, Gemma G.; Pan, Weiyi; Giammar, Daniel E.; Nguyen, Thanh H.
Highlights: After stagnation, Pb increased in preschool sinks containing point-of-use filters. Pb concentrations did not increase with stagnation in the laboratory filter setup. Preschool likely had Pb plumbing components downstream of the point-of-use filters. Point-of-use filters effectively removed chlorine in the preschool and the laboratory. Bacteria concentrations significantly increased with filtration and stagnation. Abstract: A local preschool installed NSF/ANSI 42 and 53 certified point-of-use (POU) filters in its classroom sinks and drinking fountains to protect children from the possibility of elevated lead (Pb) levels in drinking water. We examined the effects of these filters during flowing water and immediately following stagnation periods on Pb, chlorine, and bacterial concentrations in the field and the laboratory. Before and after typical school stagnation periods, we collected samples from filtered classroom sinks, a filtered drinking fountain and nearby unfiltered sinks for a year. No unfiltered samples exceeded Illinois State limits of 5 µg/L for Pb in pre-K through 5th grade schools. However, following stagnation periods as short as overnight (14.5 h), over half of post-stagnation filtered samples from classroom sinks exceeded 5 µg/L while post-stagnation unfiltered samples remained below 5 µg/L. Laboratory testing showed no significant increases in Pb with stagnation, suggesting that the preschool classrooms may have had Pb-bearing plumbing downstream of the filters which released Pb into the filtered drinking water. The filters effectively removed free chlorine (99% decrease) in both the preschool and laboratory. Installing the filters had the unintended consequence of significantly increasing the bacterial concentrations (as measured by qPCR) in the preschool's drinking water and in laboratory filter effluent. Legionella pneumophila, Pseudomonas aeruginosa, and Mycobacterium spp. were not detected in pre-stagnation unfiltered and post-stagnation filtered samples. These results suggest that the installation of POU filters be considered as one component of an overall strategy to decrease Pb concentrations in school drinking water that holistically considers the premise plumbing system. A 5-minute flush significantly decreased concentrations of Pb and bacteria in filtered sinks. Replacing Pb-bearing plumbing components downstream of a POU filter may also be needed to combat Pb levels in drinking water. Graphical abstract: Image, graphical abstract